Eye gaze technology: a South African perspective. - van Niekerk, Karin; Tönsing, Kerstin (Disability & Rehabilitation: Assistive Technology, 2015)
Purpose: Based on the bioecological model by Bronfenbrenner, this paper will provide a broad perspective on factors that need to be taken into account in order to facilitate communication and participation in preliterate children making use of electronic Augmentative and Alternative Communication (AAC) systems accessed through eye gaze. Method: Two case studies of children who have been provided with the technology described are presented. The case studies were analysed using the four nested systems of the ecology as a framework to describe not only the environment, but also the processes and interactions between the persons and their context. Results: Risk and opportunity factors are evident at all levels of the ecology. Conclusions: While a good fit between the person and the technology is an essential starting point, additional factors pertaining to the partner, the immediate environment as well as meso-, exo- and macrosystemic issues (such as societal attitudes and funding sources) have a significant influence on benefits derived. In resource-limited environments, the lack of support at more distal levels of the ecology (meso-, exo- and marosystemic levels) seems to be a factor that differentiates these environments from more resourced ones.